Theology and Poverty - Theodros Assefa Teklu (St Andrews Encyclopaedia of Theology, 2024)
This article provides an overview of the relationship between theology and poverty in the thought of the Christian church over the centuries, as well as of the interaction between theological and non-theological approaches to the conceptual study of poverty. As biblical texts are authoritative for Christians, the article starts by looking at the range of Hebrew and Greek terms used to refer to poverty, while clarifying terminological ambiguities. Then, key biblical texts and themes relating to poverty and the moral duty to the poor are theologically interpreted. Drawing on the history of Christianity, the article provides some paradigmatic examples of the church’s responses to poverty that, if appropriately harnessed, could inform contemporary Christian believers and communities in their engagement with poverty alleviation. Finally, some reflections on the interaction between theological and non-theological studies on poverty are presented, along with examples of mutual influences.